Question-based inquiry. an experience in research education - Plata Santos, María Eugenia (Universidad Pedagógica y Tecnológica de Colombia, 2011)
The present article introduces the central elements of the research and pedagogical innovation project entitled: “The Use of Questions as a Pedagogical Strategy in the Construction of Research Problems”, developed by the students of the ‘Rizoma’ research training group of the School of Psychopedagogy, which began in the year 2009, and which forms part of the “Educational Innovations” research line of the Masters sin Education Program at UPTC. The question as strategy, pedagogy or didactics, becomes an educational option for the development of thinking processes, and contributes to an education that embraces uncertainty, in order to develop flexible thinking, as well as critical and creative attitudes towards knowledge. These qualities constitute the basis of all research tasks, and are fundamental in the education of professionals in the midst of the current, fast-moving and uncertain postmodern condition. Emerging from the students’ and teacher’s own voices, this article offers an account of this experience and characterizes the findings of this education and research work.